1970
DOI: 10.1037/h0028819
|View full text |Cite
|
Sign up to set email alerts
|

Reactions to the names "Counseling Center" and "Psychological Center."

Abstract: A questionnaire administered to 376 college students on three campuses found consistent differences in the reactions which students had to the names Counseling Center (CC) and Psychological Center (PC). CC was associated with the treatment of problems which were likely to be considered minor. PC was associated with the treatment of problems which were more likely to be seen as serious. The two centers differed on a number of descriptive items, with PC being seen as more medical, expensive, professional, embarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

1972
1972
1986
1986

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…The present data lend support to earlier research findings (e.g., Kohlan, 1973;Salisbury, 1972;Sieveking & Chappell, 1970) that the title of a counseling center affects how the center is viewed by students and faculty. These data also extend our knowledge of students' help-seeking tendencies in showing that these perceptions affect anticipated use of a counseling center.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present data lend support to earlier research findings (e.g., Kohlan, 1973;Salisbury, 1972;Sieveking & Chappell, 1970) that the title of a counseling center affects how the center is viewed by students and faculty. These data also extend our knowledge of students' help-seeking tendencies in showing that these perceptions affect anticipated use of a counseling center.…”
Section: Discussionsupporting
confidence: 88%
“…Given the effects of helper titles, it also seems reasonable to hypothesize that students perceive counseling centers differently, depending on the title, and that these perceptions may affect students' use of center services. Indeed, earlier research findings may have shown that counseling center titles are perceived differently by students (Kohlan, 1973;Sieveking & Chappell, 1970) and that different types of problems are viewed as appropriate to take to different counseling centers, identified by titles (Salisbury, 1972;Sieveking & Chappell, 1970). However, it has yet to be investigated whether student willingness to use a counseling center is affected by how its title is perceived.…”
mentioning
confidence: 99%
“…Physicians did not load on a factor, but they did receive an overall high helpfulness score and were seen as especially useful for drug addicts and for those with clearly physical problems. The lower overall helpfulness rating for counselors as compared with psychologists supports the findings of a previous study (Sieveking & Chappell, 1970) that the name "Counseling Center" evoked less favorable reactions than did the name "Psychological Center." Apparently different labels for persons and for centers, which might conduct similar activities, affect the expectations that people have of them.…”
Section: Factor Vsupporting
confidence: 86%
“…The question concerning whether people seek outside help for their problems is related to studies that investigate various aspects of the decision to seek treatment (Calhoun, Dawes, & Lewis, 1972;Fisher & Cohen, 1972;Kadushin, 1958;Kalis, Harris, Prestwood, & Freeman, 1961;McMichael & Hetzel, 1974). Preferences for different sources of help have been measured by several authors (Dahms, 1969;Michael, 1967;Sieveking & Chappell, 1970); expectancies for different types of help (Johnson, 1973); or attitudes toward different clinic lables (Sieveking & Doctor, 1969). Several studies have looked at the frequency of help seeking among various groups using patients (Redlich, Hollingshead, & Bellis, 1955) or nonpatients (Fisher & Turner, 1970).…”
Section: Help Seeking Outside the Laboratorymentioning
confidence: 99%